Who's in the room? : how great leaders structure and manage the teams around them - Frisch, Bob, 1956- (San Francisco, CA. : Jossey-Bass, 2012)
'Is your company run by a team with no name?At the top of every organization chart lies a myth--that a Senior Management Team makes a company's critical decisions. The reality is that critical decisions are typically made by the boss and a small group of confidants--a'team with no name'--outside of formal processes. Meanwhile, other members of the management team wonder why they weren't in the room or even consulted ahead of time. The dysfunction that results from this gap between myth and reality has led to years of unproductive team building exercises. The problems, Frisch shows, are ones of process and structure, not psychology.Who's In the Room is based on interviews with CEOs at organizations ranging from MasterCard to Ticketmaster to The Red Cross. Understand and embrace the way decision-making actually happens in their organizations Use these'teams with no names' to best advantage Engage the Senior Management Team in the three critical tasks for which it is ideally suited Organizations will get better decisions and superior results by unleashing the full potential of their Senior Management Teams. And bosses will see a dramatic drop-off in people coming into their offices asking,'Why wasn't I in the room?''--
Includes bibliographical references and index.
Keywords: Decision making; Senior leadership teams; Chief executive officers; Executives